Self-reported and actual involvement of community pharmacists in patient counseling: a cross-sectional and simulated patient study in Gondar, Ethiopia - Surur AS; Getachew E; Teressa E; Hailemeskel B; Getaw NS; Erku DA (Centro de Investigaciones y Publicaciones Farmaceuticas, 2017)
Background: Community pharmacists play a crucial role in reducing medication related health problems and improving the patient's overall wellbeing. Evidence suggests that community pharmacist led counseling services result in a better clinical and self-reported outcome, including a higher level of satisfaction and quality of life. Objective: This study aims to document self-reported and actual levels of community pharmacists' involvement in the provision of patient counseling and barriers that limit their involvement in such services. Methods: Simulated patient visits and a cross-sectional survey of community pharmacists were employed in Gondar town, Ethiopia between March 15 and May 15, 2016 to observe actual counseling practices and to assess their reported counseling practices respectively. Four different scenarios were developed for the simulated patient visit. A well designed questionnaire and an assessment form were used for the survey and simulated patient visit. Results: In the cross-sectional survey, 84 pharmacists were approached and 78 agreed to participate (92.8 % response rate). Of the respondents, 96.1% agreed/strongly agreed that patient counseling is important and 69.3% strongly agreed that patient counseling should be a professional duty. The most frequent information provided to patients were dosing schedule of drugs, how to take medication, and drug-food interaction. Majority of community pharmacists either strongly agreed (42.1%) or agreed (51.3%) that patients are comfortable towards their counseling practice. A total of 48 simulated visits were conducted and a medicine was dispensed in all visits. In all four scenarios, dosage schedule (100%), how to take medication (97.6%) and drug-food interaction (69.1%) were the most common type of information provided while what to do when dose is missed (100%), contraindication (95.2%) and the importance of compliance or adherence (92.9%) were the most commonly ignored types of information. Conclusions: The present study emphasizes the existing gap in self-reported and actual counseling practices by community pharmacist in Gondar town, Ethiopia. Hence, the ministry of health, local health policy makers and other stakeholders should collaborate to design interventions to improve community pharmacists' dispensing and counseling practice.